(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The aim of the research is to analyze the changes in the apple production support system as a result of the Syrian crisis. In order to achieve its objectives, the research was based on the policy analysis matrix method based on preliminary data for a sample of 379 farmers randomly collected from apple farmers in Lattakia, Tartous, Hama and Al-Ghab, during the agricultural season 2020-2021, in addition to the data of the Directorate of Agricultural Economics during the 2010-2011 season. By focusing on the two most common apple varieties, Golden and Starking, in the study area. The results showed that the apple production system during the two study periods has a local competitive advantage because the financial profitability at the local market price is positive, which amounted to about 155.8 thousand SP/ha during the first period and 6.620 million SP/ha during the second period. However, the impact of the Syrian crisis was evident in the second period, after this policy managed to achieve a positive net effect during the pre-crisis period estimated at 66 thousand SP / H (equivalent to 1294.1 / H), this profit decreased as a result of the Syrian crisis and became Significantly negative during the crisis period, estimated at 58.108 SP/h (equivalent to 16.6 thousand /ha). The main reason for this is the shift in agricultural policy from focusing on supporting producers in the first period by supporting the prices of production inputs and imposing import restrictions to protect domestic prices, to supporting consumers in the second period by imposing export restrictions to maintain low domestic prices in parallel with the decline of consumers’ purchasing power, and this comes in response to the priorities of achieving food security. This is shown by the decrease in the value of the product subsidy equivalent coefficient, which changed from a positive value in the first period (0.21) to a negative value in the second period (-5.59). The bias of this policy towards consumers is also confirmed by the decrease in the value of the nominal protection factor of the outputs to 0.15 during the second period compared to 1.25 during the first period. The study concluded that if international conditions are available that allow free trade exchange, there is no justification for either of the two previous policies, but green support policies such as market reform programs and development of production infrastructure and others should be satisfied.